PENGARUH RASIO LIKUIDITAS, RASIO LEVERAGE, RASIO PROFITABILITAS DAN MARKET VALUE ADDED TERHADAP HARGA SAHAM - Annisawanti, Hilda (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This research aims to know the influence of Liquidity Ratio, Leverage Ratio,Profitability Ratio and Market Value Added to Stock Price in Sector Property, RealEstate, and Building Construction Companies Listed on Indonesia’s Stock ExchangePeriod 2012-2016. Type of research used is explanatory research. the population ofthis research came from Sector Property, Real Estate, and Building ConstructionCompanies Listed on Indonesia’s Stock Exchange which amount 59 companies and40 companies as sample using purposive sampling technique, which is determinedby some criterias. The result of partial liquidity ratio and leverage ratio have noinfluence to the stock price, profitability ratio and marketvalue added have a positiveinfluence to the stock price. Simultanly, liquidity ratio, leverage ratio, profitabilityratio and market value added give a influence to the stock price.